2013
DOI: 10.1152/ajpendo.00570.2012
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein prevents diabetes-induced cardiac pathological changes, likely via the inhibition of succinyl-CoA:3-ketoacid coenzyme A transferase-1 nitration at Trp374

Abstract: L. Metallothionein prevents diabetes-induced cardiac pathological changes, likely via the inhibition of succinyl-CoA:3-ketoacid coenzyme A transferase-1 nitration at Trp 374 . Am J Physiol Endocrinol Metab 304: E826 -E835, 2013. First published February 26, 2013 doi:10.1152/ajpendo.00570.2012.-We previously demonstrated that metallothionein (MT)-mediated protection from diabetesinduced pathological changes in cardiac tissues is related to suppression of superoxide generation and protein nitration. The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
(73 reference statements)
0
14
0
Order By: Relevance
“…However, only Trp 374 showed a significantly different nitration level between the WT and MT‐TG diabetic hearts. These results suggest that MT prevention of diabetes‐induced pathological changes in cardiac tissues is most likely mediated by suppression of SCOT nitration at Trp 374 ; In another study, using LC/MS analysis we showed that diabetes increased tyrosine nitration of the ATP synthase α subunit at Tyr271, Tyr311 and Tyr476, and the β subunit at Tyr269 and Tyr508, and also significantly reduced ATP synthase activity by ~32% (Figure ). These changes were not observed in MT‐TG diabetic mice.…”
Section: Anti‐oxidants In Dcmmentioning
confidence: 72%
See 2 more Smart Citations
“…However, only Trp 374 showed a significantly different nitration level between the WT and MT‐TG diabetic hearts. These results suggest that MT prevention of diabetes‐induced pathological changes in cardiac tissues is most likely mediated by suppression of SCOT nitration at Trp 374 ; In another study, using LC/MS analysis we showed that diabetes increased tyrosine nitration of the ATP synthase α subunit at Tyr271, Tyr311 and Tyr476, and the β subunit at Tyr269 and Tyr508, and also significantly reduced ATP synthase activity by ~32% (Figure ). These changes were not observed in MT‐TG diabetic mice.…”
Section: Anti‐oxidants In Dcmmentioning
confidence: 72%
“…3‐Ketoacid CoA transferase‐1 ( SCOT ) protein expression, nitration, and activity in the hearts of diabetic wild‐type ( WT ) and cardiac‐specific metallothionein‐overexpressing transgenic ( MT ‐ TG ) mice. Type 1 diabetes was induced with a single dose of streptozotocin ( STZ ) in Friend virus B‐type (wild‐type) and cardiac‐specific overexpression of MT ‐ TG mice used for the study. (a) Cardiac tissues collected at the indicated post‐induction times were examined by western blot to show changes in SCOT expression.…”
Section: Anti‐oxidants In Dcmmentioning
confidence: 99%
See 1 more Smart Citation
“…The bFGF supply eliminated HG-induced ROS accumulation, but bFGF with PD173074 diminished efficacy of bFGF to eliminate ROS buildup. Protein nitrations are associated with oxidative stress and lead to complications of diabetes [21], [23]. However, diabetes-induced specific protein nitrosative modifications in fibroblast cells have not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistic studies on DM effects have revealed that major causes and complications of DM are oxidative stress and nitrations of its mediated protein [21][23]. However, the events of protein nitration in fibroblasts under diabetic conditions have not been reported.…”
Section: Introductionmentioning
confidence: 99%